Filosofi Sunda dalam Konsep Lanskap Bangunan Kolonial di Kota Bandung - Husna Izzati; Andiyan Andiyan; Wowo Adizar Darwin (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2023)
Bandung has a unique landscape and is also a historic city with colonial architectural characteristics. The formation of Bandung City, could not be separated from the influence of colonialism, marked by the construction of Jalan Raya Pos. Colonial city planning was carried out by making a master plan, some with the south-north axis of the landscape concepts, but philosophically the south-north axis has been applied since the Regent of Bandung built the pendopo area. This fact raises the question of whether the concept of colonial buildings also adopts the concept of Sundanese philosophy. This study uses a qualitative method with a descriptive approach and inductive logic analysis to produce generalized conclusions. From the results of this study, it was found that there was an influence of environmental contextual aspects, considerations of morphological forms, and political aspects in designing the landscape of colonial buildings in Bandung city.